Radiologic response of chemotherapy alone versus radiation and chemotherapy in the treatment of locally‐advanced or advanced thymic epithelial tumors. Issue 10 (1st September 2020) - Chu, Robert F.; Hussien, Amira; Li, Q. Kay; Wang, Jiangxia; Friedes, Cole; Ferro, Adam; Hales, Russell K.; Battafarano, Richard; Ettinger, David S.; Voong, Khinh Ranh
Abstract : Background: Here, we investigated radiological responses following chemotherapy alone as compared to both radiation/chemotherapy (chemoRT) in patients with thymic epithelial tumors (TETs) who did not receive upfront surgery. Methods: TETs treated at a tertiary academic cancer center between January 2007 and July 2018 were identified. Patients received chemotherapy or chemoRT as initial therapy and pre‐ and post‐treatment scans were available. Student's t ‐test, Wilcoxon rank‐sum tests, and Cox proportional hazards method were used to compare clinical details and survival between groups. The primary outcome was change in tumor size, which was compared between groups using linear mixed‐effects regression models, adjusting for baseline tumor size, age, and histology. Results: A total of 24 of 114 patients with TETs identified met the inclusion criteria. The majority of patients had 67% thymoma (67%, n = 16) and AJCC8 III–IVA disease (58%, n = 14). Median age was 58.5 years (range: 33–76), median initial tumor volume was 187.1 cc (range: 28.7–653.6) and diameter was 8.5 cm (range: 4.5–14.3). Half of the patients received upfront chemotherapy ( n = 12: 83% cisplatin/adriamycin/cyclophosphamide) or chemoRT ( n = 12: 58% carboplatin/paclitaxel; median RT dose: 63 Gy [range: 60–70 Gy]). At a median imaging follow‐up of 15 months (range: 0–86): ChemoRT was associated with increased average radiological response compared to chemotherapy alone (volume: −47.0 cc more, P < 0.001; diameter: −0.8 cm more, P = 0.03). In eight patients who received chemotherapy, 33% saw further tumor shrinkage (median volume: −42.3%, P = 0.03; diameter: −3.0%, P = 0.049) with additional radiation/chemoradiation. Median survival increased for patients ultimately receiving surgery versus those who did not (46 month, range: 16–127 vs. 14 month, range: 6–82; P < 0.01). Conclusions: ChemoRT produced a greater radiologic response compared to chemotherapy alone in patients with TETs not suitable for upfront resection. Key points: Significant findings of the study: We found that chemoRT was associated with a greater radiologic response compared to patients who received chemotherapy alone. What this study adds: What this study adds: In patients with TET not amenable to upfront resection, chemoRT may be a feasible strategy for cytoreduction. Abstract : ChemoRT was associated with a greater radiologic response than chemotherapy alone in patients with upfront unresectable TET